The Islamization of the Malaysian media: a complex interaction of religion, class and commercialization - Mohamed, Shafizan; Tengku Mohd Azman, Tengku Aisha (IIUM Press, International Islamic University Malaysia, 2018)
The Islamization of the Malaysian media industry has created a debate on whether Islam has been truly adopted for its religious significance or simply manipulated for commercial gains. While Islamic content is abundant, it seems to grow in size but not in value. This paper offers a political-economic look into this problem by 1) contextualizing the Islamization process in relations to Malaysia’s socio-political environment, 2) delineating the development of Islamic media in Malaysia and, 3) identifying the influence of media ownership on the Islamization process by locating the role of Islam in contemporary Malaysian media.